Improving small-scale cultivation of Spodoptera frugiperda 9 cells by silanizing glassware - Kristina Worch; Benjamin Ole Mühlnickel; Jana Pieper; Antje Burse (Scientific Reports)
Abstract Cultivating insect cells in glass vessels can be challenging. Due to uncontrolled cell adhesion and associated cell loss as well as clumping, the replication of experiments is put at risk. A cost-effective solution to improve and stabilize cultivation may be to silanize glass vessels, making them more hydrophobic and chemically inert. Therefore, the cell growth parameters of Spodoptera frugiperda (Sf) 9 cells were characterized in an experiment comparing silanized and non-silanized vessels of three different sizes. Silanization had a significantly positive effect on living cell count and viability in small-scale cultivation (10 ml culture tubes and 50 ml culture flasks) by reducing adhesion of cells to the vessel walls. The treatment also improved the comparability of the biological replicates by reducing the variance of measurements. No such effects could be observed for larger 250 ml culture flasks. Overall, the results indicate that silanization can improve cultivation, especially when working with small glass vessels.